Twilight of the elites America after meritocracy - Hayes, Christopher, 1979- (Crown Publishers, 2012)
Analyzes scandals in high-profile institutions, from Wall Street and the Catholic Church to Major League Baseball, while evaluating how an elite American meritocracy rose throughout the past half-century before succumbing to corruption and failure